A novel D2O tracer method to quantify RNA turnover as a biomarker of de novo ribosomal biogenesis, in vitro, in animal models, and in human skeletal muscle - Brook, Matthew S.; Wilkinson, D.J.; Mitchell, W. Kyle; Lund, Jonathan N.; Phillips, Bethan E.; Szewczyk, Nathaniel J.; Kainulainen, H.; Lensu, S.; Koch, L.G.; Britton, S.L.; Greenhaff, Paul L.; Smith, K.; et al. (American Physiological Society, 2017)
Current methods to quantify in vivo RNA dynamics are limited. Here, we developed a novel stable isotope (D2O) methodology to quantify RNA synthesis (i.e., ribosomal biogenesis) in cells, animal models, and humans. First, proliferating C2C12 cells were incubated in D2O-enriched media and myotubes ±50 ng/ml IGF-I. Second, rat quadriceps (untrained, n = 9; 7-wk interval-“like” training, n = 13) were collected after ~3-wk D2O (70 atom %) administration, with body-water enrichment monitored via blood sampling. Finally, 10 (23 ± 1 yr) men consumed 150-ml D2O followed by 50 ml/wk and undertook 6-wk resistance exercise (6 × 8 repetitions, 75% 1-repetition maximum 3/wk) with body-water enrichment monitored by saliva sampling and muscle biopsies (for determination of RNA synthesis) at 0, 3, and 6 wk. Ribose mole percent excess (r-MPE) from purine nucleotides was analyzed via GC-MS/MS. Proliferating C2C12 cell r-MPE exhibited a rise to plateau, whereas IGF-I increased myotube RNA from 76 ± 3 to 123 ± 3 ng/μl and r-MPE by 0.39 ± 0.1% (both P < 0.01). After 3 wk, rat quadriceps r-MPE had increased to 0.25 ± 0.01% (P < 0.01) and was greater with running exercise (0.36 ± 0.02%; P < 0.01). Human muscle r-MPE increased to 0.06 ± 0.01 and 0.13 ± 0.02% at 3/6 wk, respectively, equating to synthesis rates of ~0.8%/day, increasing with resistance exercise to 1.7 ± 0.3%/day (P < 0.01) and 1.2 ± 0.1%/day (P < 0.05) at 3/6 wk, respectively. Therefore, we have developed and physiologically validated a novel technique to explore ribosomal biogenesis in a multimodal fashion.